In Situ Wood Fiber Dyeing Through Laccase Catalysis for Fiberboard Production - Colella, Alberto; De Chiaro, Addolorata; Lettera, Vincenzo (Frontiers in Bioengineering and Biotechnology, 2021)
The aim of the present work was to develop an innovative and environmentally friendly process for wood fiber dyeing and to produce 3-dimensionally fully colored medium-density fiberboard (MDF). The potential of laccase-catalyzed polymerization of selected precursors to form dyes useful in fiberboard manufacturing, a technique used for the first time in this field, was demonstrated. Some of the 7 aromatic compounds tested yielded colored products after laccase treatment under both acid and alkaline conditions, and a good variety of colors was attained by using mixtures of two different monomers. To demonstrate the coloration and design potential of laccase conversion of aromatic compounds, MDFs were enzymatically dyed using an in situ one-step laccase-catalyzed coloration process, and the results were compared against commercial MDFs obtained by using organic coloring agents. Important advantages over conventional processing methods include good color fastness and, in some cases, new hydrophobic properties, allowing designers and woodworkers to explore the beauty of textures and the use of simpler and milder processing conditions that eliminate harsh chemical use and reduce energy consumption.